PENCAPAIAN SAINS MAHASISWA PADA TES ISOMORFIK TIPE KUALITATIF-KUALITATIF - Sudarto, Sudarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is a pre-experimental research conducted to find out the description of the science achievements of PGSD FIP UNM Campus VI Bone students who program the Elementary Science Basic Concepts course for the even semester of the 2022/2023 lecture year on the topic of Units through a qualitative-qualitative type isomorphic test. Getting of a profile/description of the science achievements of PGSD FIP UNM Campus VI Bone students who program the Elementary Science Basic Concepts course for the even semester of the 2021/2022 lecture year on the topic of Units through qualitative-qualitative type isomorphic tests is the target to be achieved. To achieve this target, researchers explored the science abilities of students who were the target subjects by giving isomorphic qualitative-type tests. The test is in the form of a written test. The research subjects were PGSD FIP UNM Campus VI Bone students who were programming the Basic Science Concepts Course in the Even Semester of the 2022/2023 Academic Year. Data collection is carried out through recording test results. The data analysis technique uses descriptive analysis techniques. The results of the research show that the description of the students' science achievement on the Unit topic through the tests or isomorphic questions of the qualitative-qualitative type is that the average ability is in the "very good" category, the range is 26.66, the minimum score is 66.67 and the maximum score is 93 .33. The variance is 69.96, and the standard deviation is 8.12 or 9.7% of the average, which shows that the data deviation is smaller than 10%. Conclusion: through qualitative-qualitative type isomorphic questions, students achieved Science achievement in the "very good" category on the Unit topic.